Risk factors and conservative therapy outcomes of anastomotic leakage after gastrectomy: Experience of 3,926 patients from a single gastric surgical unit - He, Zhongyuan; Liu, Hongda; Zhou, Ling; Li, Qingya; Wang, Linjun; Zhang, Diancai; Xu, Hao; Xu, Zekuan (Frontiers in Oncology, 2023)
Background Anastomotic leakage (AL) after gastrectomy is one of the severest postoperative complications and is related to increasing mortality. In addition, no consensus guidelines about strategies of AL treatment have been established. This large cohort study aimed to inspect the risk factors and efficacy of the conservative treatment for AL in patients with gastric cancer. Methods We reviewed the clinicopathological data of 3,926 gastric cancer patients undergoing gastrectomy between 2014 and 2021. Results contained the rate, risk factors, and conservative therapy outcomes of AL. Results In total, 80 patients (2.03%, 80/3,926) were diagnosed with AL, and esophagojejunostomy was the most frequent AL site (73.8%, 59/80). Among them, one patient (2.5%, 1/80) died. Multivariate analysis indicated that low albumin concentration (P = 0.001), presence of diabetes (P = 0.025), laparoscopic method (P < 0.001), total gastrectomy (P = 0.003), and proximal gastrectomy (P = 0.002) were predicting factors for AL. The closure rate for the conservative treatment of AL in the first month after AL diagnosis was 83.54% (66/79), and the median time from leakage diagnosis to the closure of leakage was 17 days (interquartile range 11–26 days). Low level of plasma albumin (P = 0.004) was associated with late leakage closures. In terms of 5-year overall survival, no significant difference was observed between patients with and without AL. Conclusion The incidence of AL after gastrectomy is associated with low albumin concentration, diabetes, the laparoscopic method, and extent of resection. The conservative treatment is relatively safe and effective for the AL management in patients after gastric cancer surgery.